2001
DOI: 10.1128/mcb.21.4.1404-1415.2001
|View full text |Cite
|
Sign up to set email alerts
|

Binding of TATA Binding Protein to a Naturally Positioned Nucleosome Is Facilitated by Histone Acetylation

Abstract: The TATA sequence of the human, estrogen-responsive pS2 promoter is complexed in vivo with a rotationally and translationally positioned nucleosome (NUC T). Using a chromatin immunoprecipitation assay, we demonstrate that TATA binding protein (TBP) does not detectably interact with this genomic binding site in MCF-7 cells in the absence of transcriptional stimuli. Estrogen stimulation of these cells results in hyperacetylation of both histones H3 and H4 within the pS2 chromatin encompassing NUC T and the TATA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 65 publications
6
40
0
Order By: Relevance
“…Thus, the latter dose was used in further experiments. Incidentally, it should be noted that concentrations in the high-nM range have been largely used to investigate gene transcriptional regulation by E 2 [23][24][25][26][27] or metabolic effect of this hormone [28]. Moreover, it has been shown that intratesticular concentrations are much higher than serum levels of E 2 [29].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the latter dose was used in further experiments. Incidentally, it should be noted that concentrations in the high-nM range have been largely used to investigate gene transcriptional regulation by E 2 [23][24][25][26][27] or metabolic effect of this hormone [28]. Moreover, it has been shown that intratesticular concentrations are much higher than serum levels of E 2 [29].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have addressed the question of histone acetylation and TBP binding. In one case, TBP binding to chromatin-assembled SV40 minichromosomes was facilitated by histone acetylation at an underlying nucleosome (Sewack et al, 2001). However, in yeast gene systems, binding of TBP to promoters does not appear to strictly correlate with the acetylation status of promoter histones (Sekinger and Gross 2001;Katan-Khaykovich and Struhl 2002;Kristjuhan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation of histone tails in promoter regions facilitates efficient remodeling of nucleosomes via recruitment of SWI/SNF chromatin remodeling complexes and/or TFIID [29,33,47,48], and a recent analysis of PIC formation in 29 ENCODE regions in human cells reveals a very strong correlation between H3 acetylation and the presence of a PIC [49]. As the unmethylated promoter region of the patchmethylated cassette described here is hypo-acetylated relative to the identical but unmethylated control cassette integrated at the same site, we propose that the observed decrease in histone H3 acetylation reduces nucleosome ''fluidity'' in the promoter proximal region, which inhibits repositioning of the nucleosome around the TATA-box and in turn, recruitment of TBP.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation of histone tails neutralizes the positive charge on lysines and is believed to promote an allosteric change in nucleosome conformation that renders nucleosomal DNA more accessible to the transcription machinery [25,26], perhaps by altering higher order chromatin structure [27]. While binding of TBP to the TATA box is severely inhibited by incorporation of template DNA into a nucleosome [28], histone acetylation can facilitate TBP binding to a naturally positioned nucleosome [29]. Furthermore, in vitro and in vivo experiments are consistent with the model that histone acetylation is an early step in the cascade of events leading to transcription initiation [30][31][32][33].…”
Section: Author Summarymentioning
confidence: 99%